2018
DOI: 10.1093/jac/dky152
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of rifampicin in adult TB patients and healthy volunteers: a systematic review and meta-analysis

Abstract: ObjectivesThe objectives of this study were to explore inter-study heterogeneity in the pharmacokinetics (PK) of orally administered rifampicin, to derive summary estimates of rifampicin PK parameters at standard dosages and to compare these with summary estimates for higher dosages. MethodsA systematic search was performed for studies of rifampicin PK published in the English language up to May 2017. Data describing the Cmax and AUC were extracted. Meta-analysis provided summary estimates for PK parameter est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
71
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 47 publications
11
71
1
2
Order By: Relevance
“…28 Of note, we did not find that HIV coinfection influenced exposures of any of the antituberculosis drugs, contrary to some previous reports. [29][30][31] Our study has several limitations. First, we were unable to sample the entire trial population, which may have reduced our power to define exposure-response relationships.…”
Section: Discussionmentioning
confidence: 95%
“…28 Of note, we did not find that HIV coinfection influenced exposures of any of the antituberculosis drugs, contrary to some previous reports. [29][30][31] Our study has several limitations. First, we were unable to sample the entire trial population, which may have reduced our power to define exposure-response relationships.…”
Section: Discussionmentioning
confidence: 95%
“…A recent metanalysis found that rifampin's area under the concentration-time curve (AUC) varied 3-to 4-fold between different studies [30]. While between-laboratory differences, and genetic, environmental and pathophysiological differences between the study populations may play a role, evidence from multiple studies suggests that differences in bioavailability between formulations and batches could be responsible for large bioavailability deviations.…”
Section: Drug Formulationmentioning
confidence: 99%
“…The extent to which genetic variation governs the large differences in rifampin exposures observed between patients and between studies, is not well understood [30]. Organic-anion -transporting polypeptide1B1 (encoded by SLCO1B1) mediates transfer of rifampin into the hepatocyte, from where it is excreted via the bile.…”
Section: Pharmacogenetic Variationmentioning
confidence: 99%
“…HIV infection has a variable effect on anti‐TB drug concentrations across studies, with some studies showing lower concentrations than in HIV‐negative patients . There are few pharmacokinetic studies in HIV‐TB that assess relationships between drug exposure and clinical outcomes …”
Section: Introductionmentioning
confidence: 99%
“…Rifampicin is a potent inducer of drug metabolizing liver enzymes and also undergoes auto‐induction . The majority of rifampicin pharmacokinetic studies have been performed after administration of multiple doses when autoinduction is advanced, yet mortality in hospitalized HIV‐TB patients occurs early. In the parent cohort of this pharmacokinetic (PK) study 37% of deaths occurred within 7 days of enrolment .…”
Section: Introductionmentioning
confidence: 99%